AB0067 Total glucosides of paeony attenuated maturation of dendritic cells via blocking TLR4&5 signaling pathway leading to inhibit inflammation in vivo. (23rd January 2014) - Li, N.L.; Lin, J.L.; Zhou, Z.Z.; Huo, R.; Li, N.
Abstract : Background: Total glucosides of paeony (TGP), as active compounds extracted from the roots of Paeonia lactiflora Pall, have been recognized as an effective agent on improvement of inflammation in rheumatoid arthritis (RA) patients for more than 10 years. Nevertheless, whether TGP play roles on DCs maturation remains unknown. Objectives: This study aims to investigate the effect and mechanisms of Total glucosides of paeony (TGP) in DC maturation and its effect on inflammation alteration in vivo . Methods: TGP inhibiting DC maturation and antigen presentation was studied in Ovalbumin (OVA)-challenged inflammatory model. TGP preventing onset and clinical inflammation was examined in collagen induced arthritis (CIA) mice model. Expression of cytokines was measured by ELISA, real-time PCR and flow cytometry. Signaling and nuclear transcriptional factor profiles were detected by real-time PCR, western blotting or confocal microscopy. Results: TGP attenuated maturation of DCs selectively via blocking activation TLR4&5/MyD88/NF-kB&AP1 signaling pathway. These in turn arrested Th1 and Th17 activation and differentiation followed by inflammation reduction in OVA-challenged mice in vivo . In TGP treated CIA model, mDCs was reduced companied by down-regulated immune response against collage II and frequency of Th1/Th17, leading to delayed onset and decreased inflammatory clinical score. Conclusions: TGP arrest DCs maturation leading to reduce Th1/Th17 activation in vivo, adding a novel mechanism and therapeutic target of TGP for autoimmune diseases treatment, such as RA. Moreover, it seemed to us that TGP might be advantages in treatment RA in early-onset or an earlier resort to arresting relapse diseases trigged by re-exposure to various activators. References: Damsker JM, Hansen AM, Caspi RR. Th1 and Th17 cells: adversaries and collaborators. Ann N Y Acad Sci. 2010;1183:211-21. Dominguez PM, Ardavin C. Differentiation and function of mouse monocyte-derived dendritic cells in steady state and inflammation. Immunol Rev. 2010;234(1):90-104. Watts C, West MA, Zaru R. TLR signalling regulated antigen presentation in dendritic cells. Curr Opin Immunol. 2010;22(1):124-30. Luger D, Silver PB, Tang J, Cua D, Chen Z, Iwakura Y, et al. Either a Th17 or a Th1 effector response can drive autoimmunity: conditions of disease induction affect dominant effector category. J Exp Med. 2008;205(4):799-810. Gray P, Dagvadorj J, Michelsen KS, Brikos C, Rentsendorj A, Town T, et al. Myeloid differentiation factor-2 interacts with Lyn kinase and is tyrosine phosphorylated following lipopolysaccharide-induced activation of the TLR4 signaling pathway. J Immunol. 2011;187(8):4331-7. Zhu L, Wei W, Zheng YQ, Jia XY. Effects and mechanisms of total glucosides of paeony on joint damage in rat collagen-induced arthritis. Inflamm Res. 2005;54(5):211-20. Li J, Chen CX, Shen YH. Effects of total glucosides from paeony (Paeonia lactiflora Pall) roots on experimental atherosclerosis in rats. J Ethnopharmacol. 2011;135(2):469-75. Disclosure of Interest: None Declared